A van der Waals antiferromagnetic topological insulator with weak interlayer magnetic coupling - Chaowei Hu (Nature Portfolio, 2020)
Emergent quantum phenomena such as quantized anomalous Hall effect may be realized in magnetic topological materials. Here, Hu et al. discovered an intrinsic natural heterostructural Z2 antiferromagnetic topological insulator MnBi4Te7 with low out-of-plane saturation fields.